Transfer of Learning in People who Are Blind: Enhancement of Spatial-Cognitive Abilities through Drawing. (July 2018) - Likova, Lora T.; Cacciamani, Laura
Introduction: This study assessed whether basic spatial-cognitive abilities can be enhanced in people who are blind through transfer of learning from drawing training. Methods: Near-body spatial-cognitive performance was assessed through the Cognitive Test for the Blind (CTB), which assesses a wide range of basic spatial-cognitive skills. The CTB was administered to 21 participants who are blind in two behavioral testing sessions separated by five days. For participants in the "trained" group, these intervening days were occupied by the Cognitive-Kinesthetic Drawing Training method, during which participants learned how to draw freehand from memory. The "control" participants were not trained. Results: The results showed significantly increased overall CTB performance in the trained but not in the control group, indicating that the drawing training effectively enhanced spatial-cognitive abilities. A three- to six-month follow-up session with a subset of trained participants suggested that these training-induced spatial-cognitive improvements might persist over time, at least for some tasks. Discussion: These findings demonstrate that learning to draw from memory without vision over just five sessions can lead to enhancement of basic spatial-cognitive abilities beyond the drawing task. This study is the first to examine the transfer of learning of cognitive ability in blind individuals. Implications for practitioners: This study sheds light on the Cognitive-Kinesthetic Drawing Training as an effective wide-range rehabilitation technique that could be used to enhance basic spatial-cognitive abilities in those who are blind.